Zmiana systemów motywowania jako wynik przeobrażeń praktyki zarządzania - Kopertyńska, Maria Wanda (Change of motivation systems as a result of management practice transformation, 2005)
The commentary describes how changes commonly known as the new technical revolution, applicable to globalization processes, advances in information and telecommunication systems, increased significance of knowledge about operational processes within companies as well as other internal processes, influence changes in determining incentives and other motivational factors.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 594-601